ANALISA PERBANDINGAN LAPORAN KEUANGAN UNTUK MENILAI KINERJA KEUANGAN PADA KOPERASI SAWIT GUNUNG SANGKUR KECAMATAN KINALI KABUPATEN PASAMAN BARAT - Mardahleni Mardahleni; Nur Hamzah (Jurnal Apresiasi Ekonomi, 2016)
The financial report is the most information kursial to control a company. Analysis of the financial statements can provide information about the financial performance of a company or the other organization like Cooperative. The research carried out at the Koperasi Sawit Gunung Sangkur Kinali Kabupaen Pasaman Barat. The purpose of this study is to analyze financial performance in order to determine the development of the financial position at the Koperasi Gunung Sangkur in 2011 to 2014 period on liquidity, solvability and profitability ratio. Methodology of data analysis in this research is quantitative descriptive based on ratio analysis. Data sources are from the financial statements and the other document. The results showed that the financial performance of Koperasi Gunung Sangkur based on liquidity, solvability and profitability ratio are fluctuate from the year to year. Keywords: financial performance, liquidity ratio, solvability ratio and profitability ratio